A case of undiagnosed hyperthyroidism during anaesthesia in an adolescent. Issue 1 (8th March 2016) - Ayyash, Katie; Outram, Matthew
Summary: Childhood thyrotoxicosis is rare, with palpitations being the predominant presenting symptom [1]. Untreated patients attending for both elective and emergency surgery can develop a thyrotoxic storm intra‐operatively, a life threatening condition with a high morbidity and mortality. We present a case of suspected undiagnosed hyperthyroidism in an adolescent under anaesthesia. Our case highlights the importance of early recognition of symptoms and differentiation from other hyper‐metabolic conditions to allow early initiation of appropriate treatment, which is essential in reducing morbidity and mortality from this disorder.